ChemInform Abstract: Graphene Oxide Nanoribbons (GNO), Reduced Graphene Nanoribbons (GNR), and Multi‐layers of Oxidized Graphene Functionalized with Ionic Liquids (GO‐IL) for Assembly of Miniaturized Electrochemical Devices. Issue 23 (16th May 2013) - Valentini, F.; Carbone, M.; Palleschi, G.
Abstract Review: 171 refs.